Influence Leadership in the Implementation of Human Experience Management in Depok City Government - Huriana H.O Munthe; A. Sobandi; Edi Suryadi (Dinasti Publisher, 2025)
This study examines the influence of leadership on the implementation of Human Experience Management (HXM) within the Depok City Government. Using a qualitative approach with a case study method, the research involved 20 participants, including structural, functional, and operational officials. Data collection was conducted through in-depth interviews, participant observations, and document analysis. The findings indicate that leadership plays a pivotal role in the successful implementation of HXM, particularly in driving digital transformation and fostering changes in organizational culture. The adoption rates of HXM technology vary, with collaboration tools (90%) and employee portals (85%) showing the highest levels of usage. The transformation of the organizational culture from a hierarchical to a collaborative model has successfully enhanced employee engagement (80%) and work-life balance (85%). However, challenges such as resistance to change, technostress, and generational gaps in digital competency were identified. This study developed a comprehensive HXM implementation framework tailored to the context of local government and highlighted effective leadership practices for driving digital transformation in bureaucracy. The practical implications include the importance of a phased approach to digitalization and the development of leadership programs focused on digital competencies.